Exploring the potential neuroprotective properties of astaxanthin Nanoemulsion in modulating brain insulin resistance in Alzheimer’s disease / Dr Gurmeet Kaur Surindar Singh … [et al.] - Surindar Singh, Gurmeet Kaur; Abdul Majeed, Abu Bakar; Meor Mohd Affandi, Meor Mohd Redzuan; Jayasingh Chellammal, Hanish Singh; Mohamad Nor Hazalin, Nurul Aqmar; Arrifin, Siti Alwani; Ariffin, Nur Syamimi; Mohamed, Ruzianisra; Mohd Hatta, Fazleen Haslinda (Faculty of Pharmacy, 2023)
Freshwater and marine ecosystems are valuable sources of high-quality proteins, healthy fats, vitamins, and minerals for the human diet due to their diverse species and distinctive biodiversity. Astaxanthin, a xanthophyll carotenoids compound, has gained attention in recent years and can be acquired from seafood or isolated from the green microalga Haematococcus pluvialis for use as a dietary supplement in both humans and animals. Salmon, crab, and shrimp are all potential sources of astaxanthin. Due to its high concentration of antioxidants, astaxanthin has become a subject of interest among researchers. Studies have demonstrated that astaxanthin contains up to 1000 times the antioxidant capacity of beta carotene and vitamin E. With the potential benefits of astaxanthin in human health, researchers are actively studying its potential in treating diseases such as cancer, heart disease, diabetes, and even brain-related disease.